Fiscal, Political, and Developmental Dimensions of Decentralization: Global Insights - Irwani (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
Decentralization and regional autonomy have become central themes in governance reforms worldwide, raising critical questions about their effectiveness in improving accountability, service delivery, and socio-economic outcomes. This narrative review synthesizes existing scholarship to evaluate the effectiveness of decentralization across fiscal, political, administrative, and developmental dimensions. Literature was collected from databases such as Scopus, Google Scholar, and Web of Science, using targeted keywords and applying inclusion criteria focused on relevance, methodological rigor, and empirical evidence. The review highlights three main findings. First, fiscal decentralization demonstrates potential to enhance accountability and service delivery, but its success is constrained by elite capture and dependence on central transfers. Second, political and administrative autonomy fosters policy innovation and conflict resolution when embedded in strong institutional and legal frameworks, but in weaker contexts it may aggravate corruption and inefficiency. Third, socio-economic outcomes show significant variation: while OECD and some Asian regions report improvements in education, health, and infrastructure, many African and fragile states experience uneven benefits. These findings underscore that decentralization is not a uniform process; instead, its outcomes are shaped by systemic factors such as institutional design, political culture, and legal guarantees. Effective policy interventions should strengthen local capacity, promote transparency, and establish balanced fiscal frameworks. Future research should expand to underrepresented regions and adopt longitudinal approaches to capture long-term impacts, ensuring decentralization reforms achieve sustainable governance and inclusive development.